2023
DOI: 10.1002/solr.202201095
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic–Electrolyzer System Operated at >50 mA cm−2 by Combining Large‐Area Shingled Silicon Photovoltaic Module with High Surface Area Nickel Electrodes for Low‐Cost Green H2 Generation

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/solr.202201095.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…10,69,116,138 John et al enlarged the 4J silicon cells up to a total area of 154 cm 2 with the shingling arrangement for better space utilization, and nickel nanomeshes with a high surface area were used as the electrodes for AEM-containing electrolyzer. 141 The wire-connected PV-EC system exhibited a stable STH efficiency of 10% at a current density of B58 mA cm À2 over a durability test for 20 h in 1 M KOH under 733 W m À2 simulated illumination. For the design of large-scale PV-EC based on a silicon solar cell, Finger et al 142 firstly reported a scalable and wireless photo-voltaic water-splitting device on a 64 cm 2 scale, which consisted of 13 base units (Fig.…”
Section: From the Lab To Practical Applicationmentioning
confidence: 92%
“…10,69,116,138 John et al enlarged the 4J silicon cells up to a total area of 154 cm 2 with the shingling arrangement for better space utilization, and nickel nanomeshes with a high surface area were used as the electrodes for AEM-containing electrolyzer. 141 The wire-connected PV-EC system exhibited a stable STH efficiency of 10% at a current density of B58 mA cm À2 over a durability test for 20 h in 1 M KOH under 733 W m À2 simulated illumination. For the design of large-scale PV-EC based on a silicon solar cell, Finger et al 142 firstly reported a scalable and wireless photo-voltaic water-splitting device on a 64 cm 2 scale, which consisted of 13 base units (Fig.…”
Section: From the Lab To Practical Applicationmentioning
confidence: 92%
“…[25,60] A recently reported system of combining large-area shingled silicon photovoltaic module (6 silicon heterojunction cells with an effective area of 154 cm 2 ) with a costeffective AEM electrolyzer maintained over 20 h of operation at a high current density of 57.81 mA cm −2 , achieving an average STH efficiency of 10%, also there is no performance loss in PV and electrolyzer. [61] In recent years, significant strides have been made in largescale solar hydrogen production using concentrated photovoltaic conditions. A notable structure is the HyCon module system (Figure 11g), consisting of eight independent HyCon cells covering an area of 8 × 90.7 cm 2 , and demonstrating good stability in outdoor tests over 2 months.…”
Section: Toward Practical System Scalementioning
confidence: 99%
“…[2][3][4][5][6][7][8] Amongst the alternatives, nickel (Ni) is a well-known material and has been extensively studied for water electrolysis in alkaline media. [9][10][11][12] Particularly, nickel-iron compounds are considered as promising materials due to the synergistic effects between nickel and iron. On the anodic side, low levels of iron (Fe) incorporation from the electrolyte into the nickel electrode has a significant increase in the catalyst performance for OER.…”
Section: Introductionmentioning
confidence: 99%